Multimedia Interaktif ASWAK (Ashwat wal Kitabah) Bahasa Arab untuk Anak-anak di Kota Semarang - Dzulfiqar Saeful Islamadina; Zukhaira Zukhaira (Universitas Negeri Semarang, 2023)
Learning Arabic in schools is still a less interesting subject for students because there are several difficulties in learning it, among the difficulties experienced by students are difficulties in listening to Arabic sounds and in writing. Shame is also behind the difficulties experienced by students in learning Arabic at school. Therefore, it is necessary to develop an interactive multi-media Arabic that can motivate and increase interest in learning and interest in learning Arabic, namely ASWAK (Ashwat wal Kitabah) Arabic Interactive Multimedia for Children in Semarang City to make it easier for children to learn Arabic sounds and Arabic script writing. The problems studied in this study are (1) how to analyze the needs of teachers and children for ASWAK (Ashwat wal Kitabah) interactive multimedia. (2) how is the interactive multimedia prototype of ASWAK (Ashwat wal Kitabah), (3) how is the validation of Arabic language teaching experts and practitioners on the interactive multimedia prototype of ASWAK (Ashwat wal Kitabah), And (4) how to revise the ASWAK interactive multimedia prototype (Ashwat wal Kitabah). This research uses a mixed method and uses the ADDIE model's research and development (R&D) research design. The results of this study are as follows. First, teachers and children want the development of ASWAK Interactive Multimedia (Ashwat wal Kitabah). Second, the interactive multimedia prototype of ASWAK (Ashwat wal Kitabah) contains (1) a main page, (2) a product description, (3) choices of activities, (4) material consisting of Arabic sounds and Arabic script writing, (5) exercises, (6) instructions, and (7) developer profiles. Third, the recapitulation of the value of ASWAK interactive media (Ashwat wal Kitabah) is 3.98 with a very feasible / very appropriate category, so that Arabic Language Learning experts and teachers assess that ASWAK interactive multimedia (Ashwat wal Kitabah) can be used for children in Semarang City. Fourth, the improvement of interactive multimedia ASWAK (Ashwat wal Kitabah) Arabic from experts and teachers consists of two aspects, namely improving material aspects and improvement in the visual aspect.